Charged residues in the H-NS linker drive DNA binding and gene silencing in single cells - Gao, Yunfeng (Proc Natl Acad Sci U S A, 2017)
Nucleoid-associated proteins (NAPs) facilitate chromosome organization in bacteria, but the precise mechanism remains elusive. H-NS is a NAP that also plays a major role in silencing pathogen genes. We used genetics, single-particle tracking in live cells, superresolution microscopy, atomic force microscopy, and molecular dynamics simulations to examine H-NS/DNA interactions in single cells. We discovered a role for the unstructured linker region connecting the N-terminal oligomerization and C-terminal DNA binding domains. In the present work we demonstrate that linker amino acids promote engagement with DNA. In the absence of linker contacts, H-NS binding is significantly reduced, although no change in chromosome compaction is observed. H-NS is not localized to two distinct foci; rather, it is scattered all around the nucleoid. The linker makes DNA contacts that are required for gene silencing, while chromosome compaction does not appear to be an important H-NS function.